Tourist Destination Management - As A Tool for the Formation of Competitive Advantages of the Region - Hamidov Saidjon Komilovich (Universitas Muhammadiyah Sidoarjo, 2023)
The article analyzes the tourist destination as an element of the tourist system. Approaches to the definition of a tourist destination are considered. The features of the tourist destination as a tool for the formation of competitive advantages of the region are revealed.